Conditions that Influence Drivers' Behaviors at Roundabouts: Increasing Yielding for Pedestrians who are Visually Impaired. (January 2018) - Bourquin, Eugene A.; Emerson, Robert Wall; Sauerburger, Dona; Barlow, Janet M.
Introduction: This study examined the effects on drivers' yields of seven conditions (pedestrian behaviors) at a roundabout, measuring yielding behaviors. Methods: At a roundabout, drivers' yielding responses were recorded (none, soft, hard) when a pedestrian presented one of seven conditions: pedestrian without long cane, long cane display, hand up, reversible step (a single step forward into the street), head turn gaze, hand up plus gaze, and a reversible step plus gaze. Trials were completed at the crosswalks at the entrance and exit lanes. Results: At the entry and exit lanes, the hand up and reversible step conditions received significantly higher yield percentages than all other conditions. At the exit lanes, the reversible step condition received a significantly higher yield percentage than the hand up condition. There was no significant difference among the three head turn gaze conditions: hand up, hand up plus gaze, and reversible step plus gaze. The hand up and reversible step strategies averaged 83% yielding overall, compared with 20% yielding for the other strategies. Discussion: This study demonstrates that forced detectable yields may be generated when pedestrians have not entered the travel lanes of the street at a crosswalk or have only entered the very edge of the street. Gazing behaviors do not substantially influence drivers' yielding rates. Implications for practitioners: Using a hand up or reversible step can allow pedestrians who are visually impaired or blind to create circumstances to help determine if and when to initiate a crossing at a roundabout.